Plasma cells promote osteoclastogenesis and periarticular bone loss in autoimmune arthritis - Komatsu, Noriko; Win, Stephanie; Yan, Minglu; Huynh, Nam Cong-Nhat; Sawa, Shinichiro; Tsukasaki, Masayuki; Terashima, Asuka; Pluemsakunthai, Warunee; Kollias, George; Nakashima, Tomoki; Takayanagi, Hiroshi (The Journal of clinical investigation, 2021)
In rheumatoid arthritis (RA), osteoclastic bone resorption causes structural joint damage as well as periarticular and systemic bone loss. Periarticular bone loss is one of the earliest indices of RA, often preceding the onset of clinical symptoms via largely unknown mechanisms. Excessive osteoclastogenesis induced by receptor activator of NF-κB ligand (RANKL) expressed by synovial fibroblasts causes joint erosion, whereas the role of RANKL expressed by lymphocytes in various types of bone damage has yet to be elucidated. In the bone marrow of arthritic mice, we found an increase in the number of RANKL-expressing plasma cells, which displayed an ability to induce osteoclastogenesis in vitro. Genetic ablation of RANKL in B-lineage cells resulted in amelioration of periarticular bone loss, but not of articular erosion or systemic bone loss, in autoimmune arthritis. We also show conclusive evidence for the critical contribution of synovial fibroblast RANKL to joint erosion in collagen-induced arthritis on the arthritogenic DBA/1J background. This study highlights the importance of plasma-cell RANKL in periarticular bone loss in arthritis and provides mechanistic insight into the early manifestation of bone lesion induced by autoimmunity.